Xylem plasticity of root, stem, and branch in Cunninghamia lanceolata under drought stress: implications for whole-plant hydraulic integrity - Li, Shubin; Huang, Xiaoyan; Zheng, Ruping; Zhang, Maxiao; Zou, Zhiguang; Heal, Kate V.; Zhou, Lili (Frontiers in Plant Science, 2024)
A better understanding of xylem hydraulic characteristics in trees is critical to elucidate the mechanisms of forest decline and tree mortality from water deficit. As well as temperate forests and forests growing in arid regions, subtropical and tropical forests are also predicted to experience an increased frequency and intensity of climate change-induced drought in the near future. In this study, 1-year-old Cunninghamia lanceolata seedlings (a typical subtropical species in southern China) were selected for a continuous controlled drought pot experiment of 45 days duration. The experimental treatments were non-drought (control), light drought, moderate drought and severe drought stress, which were 80%, 60%, 50%, and 40%, respectively of soil field maximum moisture capacity. The hydraulic conductivity, specific conductivity and water potential of roots, stems, and branches of C. lanceolata all decreased with the prolonging of drought in the different drought intensities. The relative decrease in these hydraulic values were greater in roots than in stems and branches, indicating that roots are more sensitive to drought. Root tracheid diameters normally reduce to ensure security of water transport with prolonged drought, whilst the tracheid diameters of stems and branches expand initially to ensure water transport and then decrease to reduce the risk of embolism with continuing drought duration. The pit membrane diameter of roots, stems and branches generally increased to different extents during the 15–45 days drought duration, which is conducive to enhanced radial water transport ability. The tracheid density and pit density of stems generally decreased during drought stress, which decreased water transport efficiency and increased embolism occurrence. Correlation analysis indicated that anatomical plasticity greatly influenced the hydraulic properties, whilst the relationships varied among different organs. In roots, tracheid diameter decreased and tracheid density increased to enhance water transport security; stems and branches may increase tracheid diameter and pit membrane diameter to increase hydraulic conductivity ability, but may increase the occurrence of xylem embolism. In summary, under drought stress, the xylem anatomical characteristics of C. lanceolata organs were highly plastic to regulate water transport vertically and radially to maintain the trade-off between hydraulic conductivity efficiency and safety.